Identifiability, genomics and UK Data Protection Law - Curren, L; Boddington, P; Gowans, H; Hawkins, N; Kanellopoulou, N; Kaye, J; Melham, K (Martinus Nijhoff Publishers, 2010)
Analyses of individuals' genomes - their entire DNA sequence - have increased knowledge about the links between genetics and disease. Anticipated advances in 'next generation' DNA-sequencing techniques will see the routine research use of whole genomes, rather than distinct parts, within the next few years. The scientific benefits of genomic research are, however, accompanied by legal and ethical concerns. Despite the assumption that genetic research data can and will be rendered anonymous, participants' identities can sometimes be elucidated, which could cause data protection legislation to apply. We undertake a timely reappraisal of these laws - particularly new penalties - and identifiability in genomic research.